Jets in the MHD Context - Vlahakis, Nektarios (2009)
Outflows in the form of jets is a widespread phenomenon in astrophysics. Their main driving mechanism is likely related to magnetic fields. These fields are able to tap the rotational energy of the central object and its surrounding disk, and accelerate and collimate matter ejecta. To zeroth order these outflows can be described within the theory of steady, axisymmetric, ideal magnetohydrodynamics (MHD). The analytical insight into the equations of the theory (mostly on the transfield component of the momentum equation) gives simple analytical scalings for the flow speed, density, and magnetic field. The analysis is focused on nonrelativistic YSO jets; similar works [1, 2] exist for relativistic AGN, and highly relativistic GRB jets.
Keywords: physics